Respuesta :

Answer:

yes

Step-by-step explanation:

-3m+2=20

-3m=20-2

-3m=18

m=-6

Answer:

The answer is true

Step-by-step explanation:

1. Substitute -6 where you see M.

We do this is because M is equal to -6. So where we see another M, we automatically know that it is -6.

2. Rewrite the equation.

It should go from (-3m+2=20) to {-3 (-6)+2=20}

3. Solve it

-3 times -6 equals positive 18. In multiplication, a negative times a negative equals a positive. Then add the 2 and you get 20. So our answer is true.

Here's a visual walk through.

-3m+2= 20          m=-6

-3(-6)+2=20

-3(-6)= 18

18+2=20  

ACCESS MORE